Does the extended producer responsibility system promote the green technological innovation of enterprises? An empirical study based on the difference-in-differences model. (15th October 2021) - Zhao, Yinyin; Peng, Benhong; Elahi, Ehsan; Wan, Anxia
Abstract: The existing research on the impact of the extended producer responsibility (EPR) system on corporate green technological innovation is still controversial. Based on the data of Chinese manufacturing industries (collected from 2010 to 2018), the study explores the influence of the EPR system on corporate green technological innovation. The difference-in-differences method was used to solve endogeneity problems to approach study objectives. The results demonstrated that the EPR system has significantly promoted corporate green technological innovation. Specifically, the implementation of the EPR system increased the total number of green patents by 22.98%, the number of green invention patents by 35.51%, and the number of green utility model patents by 20.33%. The mechanism test showed that the EPR system could promote corporate green technological innovation through the government subsidy mechanism, but it is not significant to promote green technological innovation through corporate environmental responsibility. Similarly, heterogeneity analysis showed that the promoting effect of the EPR system on corporate green technological innovation is more significant in non-state-owned enterprises and non-high-tech enterprises. This study not only confirms the effectiveness of the EPR system in driving enterprise green technology innovation but also provides empirical evidence for Porter Hypothesis and offers practical guidance for developing countries on how to promote enterprise green technology innovation further.